IMPLEMENTATION OF FREE LEARNING POLICY-INDEPENDENT CAMPUS PROGRAMS ON MASTERING COURSE THEORY OF FOUNDATION DESIGN - Artiwi, Nila Prasetyo; Rosdiyani, Telly (ASTONJADRO, 2021)
Minister of Education and Culture Regulation No. 3 of 2020, entitles students to 3 semesters of study outside their study program. Through the Free Learning Policy - Independent Campus program, students have wide opportunity to be able to choose the learning method and place they want which is believed to be able to enrich and increase their insight and competence in the real world according to their passion and aspirations. The "Free Learning, Independent Campus" policy was initiated by the Minister of Education and Culture which includes 1) opening of new study programs, 2) higher education accreditation system, 3) freedom to become State universities with legal status, and 4) the right to study three semesters outside the study program. In planning a foundation structure, calculations must be included regarding the bearing capacity of the soil, soil stability, bearing capacity of the foundation and stability of the foundation, all of which are based on empirical and mathematical calculations. This research was conducted to analyze the level of student mastery of the Foundation Design course. With primary data collection in the form of questionnaires distributed to students of Civil Engineering, Banten Jaya University semester 7 (seven). One of the results of the research shows that students who take part in the apprenticeship program / practical work in projects with foundation work, but have not mastered the theory, most of them cannot plan and design the structure of the foundation (45 people = 84, 91%).